Odpowiedzi

2010-03-17T20:14:14+01:00
A)
/x-y=6
/y=-1

x+1=6
x=5


B)
/-x-3y=5
/y=-2x

-x+6x=5
5x=5
x=1


c)
/2x-y=4 -> 2x+2y=3y+4
/x+y=11

22=3y+4
18=3y
y=6
2010-03-17T20:15:20+01:00
A)
{x-y=6
{y=-1

x-(-1)=6
x+1=6
x=5

{x=5
{y=-1


b)
{-x-3y=5
{y=-2x

-x-3(-2x)=5
-x+6x=5
5x=5
x=1

y=-2*1
y=-2
{x=1
{y=-2


c)
{2x-y=4
{x+y=11

y=11-x

2x-11+x=4
3x=15
x=5

y=11-5
y=6

{x=5
{y=6
2010-03-17T20:18:12+01:00
A)
/x-y=6
/y=-1

x-(-1)=6
y=-1

x+1=6
y=-1

x=5
y=-1

b)
/-x-3y=5
/y=-2x

-x-3(-2x)=5
y=-2x

-x+6x=5
y=-2x

5x=5 /5
y=-2

x=1
y=-2*1

x=1
y=-2

c)
/2x-y=4
/x+y=11

2x-y=4
x=11-y

2*(11-y)-y=4
x=11-y

22-2y-y=4
x=11-y

-3y=18 /-3
x=11-y

y=-6
x=11-(-6)

y=-6
x=17

:)